EXCESSIVE MORTALITY IN WINTER IN MOSCOW AND ITS ECONOMIC VALUE DURING THE YEARS 2007-2014 - Yu. A. Balanova; A. V. Kontsevaya; M. M. Lukianov; V. G. Klyashtorny; A. S. Kuznetsov; A. M. Kalinina; S. A. Boytsov (Российский кардиологический журнал, 2015)
Aim. To study the excessive mortality during the winter (EMW) from all causes and CVD, monthly values of mortality; to evaluate social and economic harm due to EMW in Moscow.Material and methods. The calculation of EMW (%) was done for Moscow by the mortality from all causes and from CVD by a special equation. For monthly values of mortality we estimated the average range per month by absolute number of the deaths — absolute parameters of mortality by every analyzed year were ranged from 1 to 12, and mean value of the range was calculated.Results. Mean EMW per 8 years was 5,1%, for CVD higher — 8,8%. In Moscow there is an influence of the anomaly heat of 2010 — EMW was 4,5% from all causes, from CVD — 6,0%. Maximum number of deaths was registered in January and march. Gross EH by 2007-2013 from EMW was 7,9 billion rubles in Moscow.Conclusion. A significant part of EMW are the deaths from CVD. The amount of EH from EMW has confirmed the shown previously relation from two factors — number of deaths and size of GRP in region. For Moscow — the capital of Russia, having the highest values of economic development, the harm, that is quite significant, grounds the necessity of investments into excessive mortality and search for effective by decrease of mortality in winter time.